Fear of missing out and Generation Z’s investment behavior in Vietnam’s stock market: The moderating role of financial literacy - Nguyen, Kim Thi Chung; Dao, Thi Ho Huong; Pham, Van Phat; Nguyen, Pham Hoang Nam (Edelweiss Applied Science and Technology, 2026)
This study investigates the impact of the Fear of Missing Out (FOMO), specifically across group, individual, and influencer dimensions, on the investment behavior of Generation Z in Vietnam, while examining the moderating role of financial literacy. Utilizing a large-scale survey of 5,441 Gen Z investors and employing the PLS-SEM model, the research analyzes the interaction between psychological drivers and financial capability, showing that FOMO dimensions significantly drive impulsive investment decisions, with media influencers exerting the strongest impact. Crucially, the results demonstrate that personal financial literacy, at both basic and advanced levels, plays a negative moderating role, effectively shielding young investors from the adverse effects of FOMO. The study concludes that while psychological biases are prevalent in emerging markets, financial knowledge is a vital mechanism for rationalizing investment behavior. These insights imply a critical need for educational institutions and market regulators to develop targeted financial education programs and market supervision strategies to foster sustainable investing among the digital generation.